Preferential quadriceps activation in female athletes with incremental increases in landing intensity - Ford, K. R.; Myer, G. D.; Schmitt, L. C.; Uhl, T. L.; Hewett, T. E. (Journal of Applied Biomechanics, 2011)
The purpose of this study was to identify alterations in preparatory muscle activation patterns across different drop heights in female athletes. Sixteen female high school volleyball players performed the drop vertical jump from three different drop heights. Surface electromyography of the quadriceps and hamstrings were collected during the movement trials. As the drop height increased, muscle activation of the quadriceps during preparatory phase also increased (p < .05). However, the hamstrings activation showed no similar increases relative to drop height. Female athletes appear to preferentially rely on increased quadriceps activation, without an increase in hamstrings activation, with increased plyometric intensity. The resultant decreased activation ratio of the hamstrings relative to quadriceps before landing may represent altered dynamic knee stability and may contribute to the increased risk of ACL injury in female athletes.